دور الإدارة الإلكترونية في تحسين أداء محطة حاويات مرفأ اللاذقية - نادر نهاد; الشهدا ايهم (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى التعرف على دور الإدارة الإلكترونية في تحسين أداء محطة حاويات مرفأ اللاذقية من خلال دراسة العلاقة بين كل من التخطيط الإلكتروني، والتنظيم الإلكتروني، والتنفيذ الإلكتروني، والرقابة الإلكترونية، وبين تحسين أداء محطة حاويات مرفأ اللاذقية. اعتمد البحث المنهج الوصفي، وشمل مجتمع البحث المستفيدين من خدمات محطة حاويات مرفأ اللاذقية من وكلاء بحريين ومخلصين جمركيين، والبالغ عددهم (68) مستفيداً يعملون بشكل فعلي، حيث تمّ استقصاءُ آرائهم باستخدام طريقة الحصر الشامل، وتمّت استعادة (65) استمارة كاملة وصالحة للتحليل الإحصائي، وكان من أهم نتائج البحث: 1- وجود علاقة طردية ومتينة بين التخطيط الإلكتروني وأداء محطة حاويات مرفأ اللاذقية، حيث إنّ (70.9%) من التغيرات الحاصة في أداء محطة الحاويات يفسرها التخطيط الإلكتروني. 2- وجود علاقة طردية ومتينة بين التنظيم الإلكتروني وأداء محطة حاويات مرفأ اللاذقية، حيث إنّ (78.5%) من التغيرات الحاصة في أداء محطة الحاويات يفسرها التنظيم الإلكتروني. 3- هناك علاقة طردية ومتينة بين التنفيذ الإلكتروني وأداء محطة حاويات مرفأ اللاذقية، حيث إنّ (64.3%) من التغيرات الحاصة في أداء محطة الحاويات يفسرها التنفيذ الإلكتروني. 4- هناك علاقة طردية ومتينة بين الرقابة الإلكترونية وأداء محطة حاويات مرفأ اللاذقية، حيث إنّ (69.6%) من التغيرات الحاصة في أداء محطة الحاويات تفسرها الرقابة الإلكترونية. 5- يتميز أداء محطة حاويات مرفأ اللاذقية بالكفاءة نتيجة استخدام نظام التشغيل TOS، حيث تقوم المحطة من خلال هذا النظام في التخطيط والاستقبال والترصيف للسفن، وفي تبادل المعلومات إلكترونياً داخل أقسام المحطة ومع الجهات الخارجية، وفي التقليل من زمن مكوث الحاوية في المحطة. The research aims to identify the electronic management role in improving the performance of Lattakia Port Container Terminal through the study of the relationship between each of the mail planning, organizing mail, execution-mail, electronic controls, and improve the performance of Lattakia Port Container Terminal. Adopted Find descriptive approach, and included the research community beneficiaries of the container port of Latakia agents offshore and sincerely customs agents terminal services, totaling (68) are working effectively, where BI views using the comprehensive inventory, has been restored (65) complete and valid for statistical analysis form, One of the most important results: 1- there is a positive and strong relationship between planning and performance-mail Lattakia Port Container Terminal, where that (70.9%) of alopecia changes in the container terminal interpreted mail planning performance. 2- there is a positive and strong relationship between the organization and the performance of mail Lattakia Port Container Terminal, where that (78.5%) of alopecia changes in the container terminal performance interpret electronic organization. 3- There is a positive and strong relationship between electronic execution and performance of Lattakia Port Container Terminal, where that (64.3%) of alopecia changes in the container terminal performance interpreted execution-mail. 4- There is a positive and strong relationship between the electronic control and the performance of Lattakia Port Container Terminal, where that (69.6%) of alopecia changes in the container terminal interpreted by the electronic control performance. 5- Lattakia port container terminal performance is characterized by the use of efficient TOS operating system, where the station through this system in the planning and the reception and docking of ships, and the exchange of information electronically inside the station sections and with third parties, and to reduce the stay of the container terminal in time.